Twice - Albom, Mitch, 1958- (London : Sphere, 2025)
"What if you got to do everything in your life -twice? The heart of Mitch Albom's newest novel is a love story that dares to explore how our unchecked desires might mean losing what we've had all along"-- Provided by publisher.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Boys -- Fiction; Choice (Psychology) -- Fiction; Gambling -- Fiction; Love -- Fiction; Men -- Fiction; Man-woman relationships -- Fiction; Opportunity -- Fiction; Time travel -- Fiction